Left or right, up or down: A case for positioning of unconcious head-injured patients - M. Hugo (AOSIS, 1992)
Nursing care activities have been proved to cause increases in intracranial pressure (ICP) which could be detrimental to the patient's health. Because positioning is one of the activities that causes the greatest pressure changes it was evaluated in this study. Cumulative increases also occur when nursing care activities are carried out in quick succession. The analysis of the data and literature suggest that the backrest position with the head of the bed elevated 30 to 45 degrees is the best position for a patient with increased ICP. If further research should prove that this position has a negative influence on the cerebral perfusion pressure, these recommendations will have to be revised.